Interactive Teaching Material Design for Learning Anecdote Text Based on Riau Malay Stories for Students - Kartika, Amelia; Asnawi (UNDIKMA, 2026)
This study aims to design and develop interactive teaching materials for anecdote text learning based on Malay Riau stories for tenth-grade students at Uperta Integrated Agricultural Vocational High School (SMKN Pertanian Terpadu) in Pekanbaru City. This development is motivated by students’ low interest in understanding anecdote texts, which tend to be abstract and lack connection to local cultural contexts. The research employed the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results indicate that the interactive teaching materials based on Malay Riau culture effectively enhance student engagement and are valid and feasible for use according to assessments by media experts, language experts, and subject matter experts.